Mindful sport performance enhancement mental training for athletes and coaches - Kaufman, Keith A.; Glass, Carol R.; Pineau, Timothy R. (Washington, DC American Psychological Association, 2018)
All athletes and coaches know that peak performance requires more than just physical exertion. There is a psychological component as well, which can be expressed in attributes such as awareness, focus, emotion regulation, and motivation. For many years, systematic mental training was ignored in athletics. Thankfully, this is the starting change. This comprehensive resource on the history, theory, and practice of mindfulness in sport offers a fresh, exciting approach to performance enhancement for athletes and coaches at all levels, from amateur to professional. Rooted in the traditions of mindfulness-based stress reduction and mindfulness-based cognitive therapy, Kaufman, Glass, and Pineau present mindful sport performance enhancement (MSPE), an empirically supported, six-session program that can be adapted for athletes or even performers in other high-pressure domains. Each MSPE sessions includes educational, experiential, and discussion components, as well as recommendations for home practice. There is special emphasis on incorporating mindfulness into workouts, practices, and competitions, as well as everyday life. The book includes handy scripts for mindfulness teachers, sport and performance psychologists, athletes, and coaches, and handouts summarizing each session are also available for download at http://pubs.apa.org/books/supp/kaufman/.
1. Overcoming the mental training paradox -- 2. The long past but short history of mindfulness in sport -- 3. Going with the flow: mindfulness and peak performance -- 4. MSPE session 1: building mindfulness fundamentals -- 5. MSPE session 2: strengthening the muscle of attention -- 6. MSPE session 3: stretching the body's limit mindfully -- 7. MSPE session 4: embracing "what is" in stride -- 8. MSPE session 5: embodying the mindful performer -- 9. MSPE session 6: ending the beginning -- 10. Pathways from MSPE to peak performance -- 11. Empirical support for MSPE -- 12. Tips for participants: getting the most out of MSPE -- 13. Tips for leaders: enhancing the effectiveness of MSPE -- 14. Performance applications beyond sport -- 15. Case study 1: John the outfielder -- 16. Case study 2: Angie the basketball coach
Foreword by Jon Kabat-Zinn
Keywords: Sports -- Psychological aspects; Athletes -- Psychology